An experimental investigation on vortex induced vibration of a flexible inclined cable under a shear flow. (April 2015) - Chen, Wen-Li; Zhang, Qiang-Qiang; Li, Hui; Hu, Hui
Abstract: In the present study, an experimental investigation was performed to characterize the vortex induced vibration (VIV) of a flexible cable in an oncoming shear flow. The VIV tests were conducted in a wind tunnel with a flexible cable model. It was found that, under different oncoming velocity profiles, the cable model behaved in single-mode and multi-mode VIVs. The displacement amplitudes of the single mode VIVs were found to be larger than those of multi-mode VIVs, and the cross-flow (CF) response was larger than that of in-line (IL) direction for either the single mode or multi-mode VIVs. For a single mode vibration, the largest CF response occurs in the 1st mode VIV, and the motion trajectory of the 1st mode VIV was found to be an inclined figure of eight shape, while other single mode VIVs behaved in ellipse or straight line trajectories. For multi-mode VIVs, no stable vibration trajectories were found to exist since the vibration frequency bands covered two or more vibration modes. The vortex-shedding frequencies in the wake behind the inclined cable were also characterized in the present study. The shedding frequencies of the wake vortices were found to coincide well with the vibration modes: for a single mode VIV, they were close to the dominant vibration mode; for a multi-mode VIV, they could also cover the appearing vibration modes. Highlights: An experimental investigation was conducted to characterize the vortex induced vibration (VIV) of a flexible cable in an oncoming shear flow. Under different oncoming velocity profiles, the cable model behaved in single-mode and multi-mode VIVs. Single-mode VIVs behave in stable trajectories and multi-mode VIVs have no stable trajectories. For a single mode VIV, shedding frequencies were close to the dominant vibration modal frequencies. For a multi-mode VIV, shedding frequencies can cover the appearing vibration modal frequencies.